2016
DOI: 10.1016/j.ttbdis.2016.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Babesia bovis and Babesia bigemina infection levels estimated by qPCR in Angus cattle from an endemic area of São Paulo state, Brazil

Abstract: The levels of infection by Babesia bovis and Babesia bigemina were estimated by absolute quantification through the quantitative PCR technique (qPCR). Fifty-one contemporaneous Angus cattle were evaluated on two occasions. The number of standard female Rhipicephalus microplus ticks present on the left side of the body was counted and blood samples were drawn from the tail vein into tubes containing the anticoagulant EDTA. The blood samples were submitted to DNA extraction and used to quantify the number of cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 36 publications
8
23
1
Order By: Relevance
“…All the animals were positive for B. bovis in both collections. The high sensitivity of qPCR to assess the level of infection by B. bovis has also been reported by Bilhassi et al (2014) and Giglioti et al (2016).…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…All the animals were positive for B. bovis in both collections. The high sensitivity of qPCR to assess the level of infection by B. bovis has also been reported by Bilhassi et al (2014) and Giglioti et al (2016).…”
Section: Discussionmentioning
confidence: 59%
“…With respect to the fluctuation in the quantity of DNA from the hemoparasite in the animals' blood, it is hard to determine the cause. Considering the repeatability values found for the NC metric, we can infer that a large part of this variation can be attributed to environmental factors that act on the animal at the collection time, and only a small part can be attributed to the animals' ability to maintain low infection levels, as also verified by Giglioti et al (2016). Although tick infestation can vary between collections, previous studies have shown no association between tick count and NC (Giglioti et al, 2016) and indicate this cannot be reported as the cause of the variation.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The diagnosis of these diseases in clinically affected animals is usually made through of microscopic examination of peripheral blood smears (Bock et al, 2004;Calder et al, 1996;Sahinduran, 2012). The detection of carrier animals requires the use of more sensitive techniques as PCR and qPCR Oliveira-Sequeira et al, 2005;Buling et al, 2007;Ramos et al, 2011;Bilhassi et al, 2014;Giglioti et al, 2016;Giglioti et al, 2017).…”
mentioning
confidence: 99%